Molecular genetics studies on olives - Alsamman Mahmoud Mohammed Ali Alsamman; Basita Abbas Hussein; Ebtissam Hussein Aly Hussein; Sami Said Adawy (Cairo : Alsamman Mahmoud Mohammed Ali Alsamman, 2017)
The genetic diversity among ten olive (Olea europaea) varieties was assessed using three molecular markers systems i.e., RAPD, SCoT and SAMPL. In addition, a new type of markers namely Selective Amplification of Start Codon Polymorphic Loci (SASPL) marker was developed. SASPL was validated in vitro by testing the genetic diversity among the ten olive varieties and the results were compared with that of RAPD, SCoT and SAMPL. Assesment also included primer selectivity, genome coverage and the ability to target genic regions using in silico PCR analysis. Finally, selected candidate PCR amplicons were sequenced to investigate the possibility to identify anonymous genes of olive. Eight SASPL primers were compared to 24 RAPD, 39 SCoT and 12 SAMPL primers. The total number of amplicons (TA) produced by the RAPD, SCoT, SAMPL and the eight SASPL primers were 359, 642, 571 and 269 amplicons, respectively. SAMPL revealed the highest average number of TA (47.6), average of polymorphic amplicons (PA) (18.1) and genetic similarity (GS) (96%) among the olive varieties. On the other hand, SASPL analysis provided higher average number of TA (33.6), average PA (16.2) and GS (93%) than SCoT and RAPD. The highest average of polymorphic information content (PIC) (0.2909) was exhibited by SASPL and the lowest average (0.2038) was revealed by SCoT. The highest number of unique bands (UB (111) was revealed by SCoT and the lowest UB (43) was obtained by SASPL. Across the four marker types, variety Maraki was characterized by the highest number of unique markers (74). Meanwhile, the variety Manzanillo was characterized by the lowest number of unique markers (8). In addition, in the in silico analysis SASPL exhibited the highest chromosomal coverage (0.59%) and targeted genes (1090) using the lowest number of primers. Additionally, the average area covered by the SASPL primers (354kb) was larger than SCoT and SAMPL. RAPD analysis provided the lowest potential, chromosomal coverage (0.04%) and number of targeted genes (17) compared to SASPL, SCoT and SAMPL analysis
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture- Department of Genetics
Issued also as CD
Keywords: Olive; RAPD; SCoT